2020
DOI: 10.1136/annrheumdis-2020-217259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of fasinumab in patients with chronic low back pain: a phase II/III randomised clinical trial

Abstract: ObjectivesTo study the efficacy and safety of fasinumab in moderate-to-severe, chronic low back pain (CLBP).MethodsIn this phase II/III, double-blind, placebo-controlled study, patients with CLBP aged ≥35 years with inadequate pain relief/intolerance to acetaminophen, non-steroidal anti-inflammatory drugs and opioids were randomised to fasinumab 6 or 9 mg subcutaneous every 4 weeks (Q4W), 9 mg intravenous every 8 weeks (Q8W) or placebo. Primary endpoint was change from baseline to week 16 in average daily low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…ADA reflects the cell mediated immunity and also involved in maturation of lymphocytes and their function, formation of macrophages from monocytes 9 . RA is associated with increased levels of ADA in the serum and synovial fluid of joints 10 , 11 . ADA has been suggested as a marker to evaluate disease activity in RA by previous studies 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…ADA reflects the cell mediated immunity and also involved in maturation of lymphocytes and their function, formation of macrophages from monocytes 9 . RA is associated with increased levels of ADA in the serum and synovial fluid of joints 10 , 11 . ADA has been suggested as a marker to evaluate disease activity in RA by previous studies 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Thirty studies ( Berry and Hutchinson, 1988 ; Stein et al, 1996 ; Birbara et al, 2003 ; Ruoff et al, 2003 ; Coats et al, 2004 ; Pallay et al, 2004 ; Peloso et al, 2004 ; Kanayama et al, 2005 ; Perrot et al, 2006 ; Pareek et al, 2009 ; Skljarevski et al, 2009 ; Skljarevski et al, 2010a ; Skljarevski et al, 2010b ; Buynak et al, 2010 ; Hale et al, 2010 ; Katz et al, 2011 ; Biondi et al, 2013 ; Kivitz et al, 2013 ; Rauck et al, 2014 ; Tiseo et al, 2014 ; Friedman et al, 2015 ; Rauck et al, 2015 ; Baron et al, 2016 ; Bedaiwi et al, 2016 ; Gottlieb and Njie, 2016 ; Konno et al, 2016 ; Sanga et al, 2016 ; Miki et al, 2018 ; Dakin et al, 2020 ; Markman et al, 2020 ) were included in this NMA ( Supplementary Figure S1 ). Nine groups were included in the main network analysis: placebo (Pla), antidepressant (ADP), anti-NGF (ANGF), acetanilide antipyretic analgesics (AP), nonsteroidal anti-inflammatory drugs (NSAIDs), weak opioids (WO), strong opioids (SO), a combination of AP and WO (cAPWO), and a combination of NSAIDs and skeletal muscle relaxants (cNSMRs).…”
Section: Resultsmentioning
confidence: 99%
“…The contrasting NGF tissue distribution between facet joint and knee OA might provide insight into the frequency of RPOA as adverse events in NGFi treatment. Recent studies have demonstrated a dose-dependent increase of RPOA in patients with knee OA or CLBP treated with NGFi ( 10 , 11 ), yet this rarely occurred in CLBP patients without peripheral OA. NGF has been described as a regulator of osteogenesis and bone turnover ( 16 ), however, scarce expression in bone marrow would argue against a significant contribution of NGF signalling to FJOA bone remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed efficacy of NGFi in improving pain and physical function in knee OA, while RPOA remained a serious adverse event in 1-3% of the treated patients ( 10 ). In a cohort of chronic CLBP patients NGFi demonstrated efficacious in reducing CLBP intensity and RPOA was almost exclusively observed in individuals with additional peripheral OA ( 11 ).…”
Section: Introductionmentioning
confidence: 99%